MANDUPI (Etlingera rubroloba A.D Poulsen): TINJAUAN KANDUNGAN METABOLIT DAN AKTIVITAS FARMAKOLOGINYA - Tahoangako, Sarmadhan Saputra (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Etlingera rubroloba A.D Poulsen, a member of the Zingiberaceae family. Etlingera rubroloba A.D Poulsen is a locally known plant such as Mandupi (Muna), Kasimpo (Makassar), Pane (Bugis) and Wualae (Tolaki). This plant has been widely used empirically as a remedy for muscle pain and gout, particularly among the people of Sulawesi. Mandupi (Etlingera rubroloba A.D Poulsen) contains secondary metabolite compounds in the form of alkaloids, flavonoids, saponins, terpenoids, and tannins. This aim of this study is to identify the pharmacological activities of the chemical compounds present in Mandupi through a literature review of various related journals. The results of various studies indicate that Mandupi has pharmacological activities such as antibacterial, antihyperuricemia, antioxidant, anti-inflammatory and immunomodulator.